Code-Mixing on Social Media: A Case Study among Acehnese Youngsters - Dara Yusnida; Ida Muliawati (Proceedings of AICS - Social Sciences, 2021)
This research aims at investigating kinds of code-mixing frequently used by Acehnese youngsters on their social media and factors interfering with it. The indicator forms of the researcher used in the level of code-mixing are words, phrase, clause, baster, idiom, and repetition level, while types of code mixing assessed are creative spelling, phonetic typing, word play, abbreviation and meta tags. The research magnified a descriptive qualitative method in which Instagram and WhatsApp’s documents (status, caption, feed, and comment) were observed to get data. Still, a questionnaire was also applied to find out the reasons behind the use of code-mixing among 50 respondents who were selected by using purposive sampling. Result of the research from the respondents’ social accounts reveals that the majority of the respondents used code-mixing in phrase level, while none of them used idiom level. Still, the type of code-mixing frequently used on their social platforms to run online communication is spelling errors. The result of the questionnaire nails some factors behind the usage. Most of the respondents chose to use code-mixing because they want to learn and understand new words by inserting them in sentences. Meanwhile, only some of them felt that to look cool and smart is the reason for using code-mixing on their social media.Keywords: code, code-mixing, social media, youngster.